2010
DOI: 10.1097/opx.0b013e3181d951c8
|View full text |Cite
|
Sign up to set email alerts
|

Amblyopia in Astigmatic Infants and Toddlers

Abstract: Purpose To determine if reduced astigmatism-corrected acuity for vertical (V) and/or horizontal (H) gratings and/or meridional amblyopia (MA) are present prior to age three years in children who have with-the-rule astigmatism. Methods Subjects were 448 children, 6 months through 2 years of age with no known ocular abnormalities other than with-the-rule astigmatism, who were recruited through Women, Infants and Children clinics on the Tohono O’odham reservation. Children were classified as non-astigmats (≤ 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…The visual system may not be very sensitive to uncorrected astigmatism in the first year of life 54 but from one year onwards, there is evidence that uncorrected astigmatism, particularly oblique astigmatism, is associated with meridional amblyopia 20,25,55 . Dobson and colleagues 56 found no evidence of meridional amblyopia in six‐month‐olds up to three‐year‐olds with astigmatism of 2.00 D or more, although the acuity for both vertical and horizontal gratings was decreased in children with astigmatism, which may be because most of the children with astigmatism were also hyperopic. In three‐ to four‐year‐olds, 1.50 D or more of astigmatism is associated with poorer recognition acuity, such that for every dioptre increase in cylinder, there was a half‐line decrease in VA 57 .…”
Section: Infants and Children From Birth To Six Yearsmentioning
confidence: 99%
“…The visual system may not be very sensitive to uncorrected astigmatism in the first year of life 54 but from one year onwards, there is evidence that uncorrected astigmatism, particularly oblique astigmatism, is associated with meridional amblyopia 20,25,55 . Dobson and colleagues 56 found no evidence of meridional amblyopia in six‐month‐olds up to three‐year‐olds with astigmatism of 2.00 D or more, although the acuity for both vertical and horizontal gratings was decreased in children with astigmatism, which may be because most of the children with astigmatism were also hyperopic. In three‐ to four‐year‐olds, 1.50 D or more of astigmatism is associated with poorer recognition acuity, such that for every dioptre increase in cylinder, there was a half‐line decrease in VA 57 .…”
Section: Infants and Children From Birth To Six Yearsmentioning
confidence: 99%
“… 7 , 8 Second, the presence of marked astigmatism during the development of the visual system can cause meridional amblyopia in children. 9 , 10 Finally, this type of refractive error may disturb emmetropization due to producing a blurred image on the retina. 11 , 12 Other studies have shown that uncorrected astigmatism can result in the formation or progression of myopia, as well.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 13 , 14 Most changes due to astigmatism and its effects, especially its amblyogenic and myopigenic nature, are observed in individuals under 15 years of age. 9 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…While astigmatism comprises cornea and non-corneal components, it typically results from the unequal curvature of two principle meridians in the anterior surface of the cornea known as corneal astigmatism [1] , [2] . The presence of a high degree of astigmatism during early development is believed to be associated with refractive amblyopia [3] , [4] , [5] , as evidenced by decreased best-corrected visual acuity which cannot be remedied by external corrective lenses. Early abnormal visual input caused by uncorrected astigmatism can lead to orientation-dependent visual deficits, despite optical correction of visual acuity later in life [6] .…”
Section: Introductionmentioning
confidence: 99%